Identifikasi Senyawa Metabolit Sekunder Ekstrak Jamur Tiram Putih (Pleurotus ostreatus L.) - Intan Apri Resti; Hesty Parbuntari (Departemen Kimia FMIPA UNP, 2022)
Pleurotus ostreatus are fungi from the family of agaricaceae or a type of mushroom that grows in wood and is usually consumed by the Indonesian people and cultivated with a simple technique. Pleurotus ostreatus have a lot of nutrients and contain secondary metabolites that can affect the use of bioactive properties as drug compounds. In this study phytochemical screening was conducted to determine the secondary metabolite compound contained in Pleurotus ostreatus. The results of phytochemical screening show that Pleurotus ostreatus contain secondary metabolite compounds of alkaloids, steroids and saponins, but do not contained terpenoid and flavonoid compound.